02 ANALISIS PERBANDINGAN PENDAPATAN PETANI PADI SAWAH BERDASARKAN PENGUASAAN LAHAN DI LINGKUNGAN PUTE KELURAHAN MACCINI BAJI KECAMATAN LAU KABUPATEN MAROS - Jurnal Agribis; Megawati Megawati; Mohammad Anwar Sadat; Abd. Asis Pata (Universitas Muslim Maros, 2020)
Paddy rice commodity is one of the most important and strategic food crops as a source of supply of basic food needs in the form of rice. This research was carried out in the Pute Environment of Maccini Baji Village, Kecaatan lau, Maros Regency. This research aims to analyze the income of rice farmers based on land tenure. To take a sample the Simple Random Sampling Method is used. The data used are twofold: primary data that is data obtained directly from observations through direct interviews and also through the help of questionnaire lists and peer data that is data obtained from agencies / institutions that are related or related to this research. The purpose of this study: Determine the amount of income of the owner and non-owner farmers based on land tenure in the pute environment and the ratio of the income of the owner and non-owner farmers in terms of age, education level, farming experience, family dependents, land area and income of the owner and farmers non-owner farmers. Data collected from survey results using a questionnaire and added to observations / field observations. The collected data is then tabulated to obtain real data used for analysis. This study uses a quantitative descriptive analysis method to obtain an analysis of farmers' income and a comparison of the income of non-owner rice farmers and landowners in the Pute Environment of Maccini Village, Baji Lau District, Maros District. Maccini wages Lau Savings Maros district is the production, grain prices, receipts, farming costs and total income and income difference of farmers. Suggestions given are so that farmers can follow the cultivation recommended by PPL and improve the cultivation techniques carried out so far so that rice production can increased.